IMPLEMENTASI PEMBELAJARAN KOOPERATIF NUMBERED HEADS TOGETHER SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR SISWA - Yuyun Bahtiar; Nurul Anwar (Edudeena : Journal of Islamic Religious Education, 2020)
Abstract: The low learning outcomes of PAI grade VII A students of SMP I Megaluh Jombang, need to be improved and improved as well as finding solutions so that the quality of PAI learning increases. Through the application of learning Numbered Heads Together in learning process can encourage students to be active and directly involved in learning such as solving problems, dare to express opinions, respect the opinions of others so that learning is more alive and students are encouraged to prepare themselves well. Then it will increase attention, interest and motivate learning and encourage the creation of participatory learning. The research objective is to determine the learning outcomes of PAI and determine the supporting and inhibiting factors using NHT type learning. The study design includes planning, implementation, observation/field notes, and reflection. The research subjects of class VII A of SMP I Megaluh, odd semester of 2014/2015 were 30 students. Data collection techniques in the form of tests, observations/field notes and documentation, then the data were analyzed using qualitative descriptive statistics. The results of the management and analysis of the data can be concluded that through the application of NHT learning model in the learning process it turns out the learning outcomes about the prayers of Grade VII A students of SMP I Megaluh can be improved. Abstrak: Rendahnya hasil belajar PAI siswa kelas VII A SMPN I Megaluh Jombang, perlu diperbaiki dan ditingkatkan serta dicarikan solusi agar supaya meningkat kualitas pembelajaran PAI. Melalui penerapan pembelajaran Numbered Heads Together pada proses pembelajaran bisa mendorong siswa aktif dan terlibat langsung dalam pembelajaran seperti memecahkan masalah, berani mengeluarkan pendapat, menghargai pendapat orang lain sehingga pembelajaran lebih hidup dan siswa terdorong untuk mempersiapkan diri dengan baik. Kemudian akan meningkatkan perhatian, minat dan memotivasi belajar serta mendorong terciptanya pembelajaran partisipatif. Tujuan penelitian untuk mengetahui hasil belajar PAI dan mengetahui faktor penunjang serta penghambat dengan menggunakan pembelajaran tipe NHT. Rancangan penelitian meliputi perencanaan, pelaksanaan, obesrvasi/pengamatan, dan refleksi. Subjek penelitian siswa kelas VII A SMPN I Megaluh, semester ganjil Tahun 2014/2015 berjumlah 30 siswa. Teknik pengumpulan data berupa tes, observasi/catatan lapangan dan dokumentasi, kemudian data dianalisis menggunakan statistik deskriptif kualitatif. Hasil pengelolaaan dan analisis data bisa disimpulkan bahwa melalui penerapan model pembelajaran NHT dalam proses pembelajaran ternyata hasil belajar tentang sholat siswa kelas VII A SMPN I Megaluh bisa meningkat